Chemoorganotrophic Bacteria From Lake Fryxell, Antarctica, Including Pseudomonas Strain LFY10, a Cold-Adapted, Halotolerant Bacterium Useful in Teaching Labs - Baker, Jennifer M.; Vander Schaaf, Nicole A.; Cunningham, Anna M. G.; Hang, Anna C.; Reeves, Chelsea L.; Huffman, Emily R.; Riester, Carli J.; Madigan, Michael T.; Sattley, W. Matthew (Frontiers in Microbiology, 2019)
Lake Fryxell, situated in the McMurdo Dry Valleys of Antarctica, is an intriguing aquatic ecosystem because of its perennial ice cover, highly stratified water column, and extreme physicochemical conditions, which collectively restrict lake biodiversity to solely microbial forms. To expand our current understanding of the cultivable biodiversity of Lake Fryxell, water samples were collected from depths of 10 m and 17 m, and pure cultures of eight diverse strains of aerobic, chemoorganotrophic bacteria were obtained. Despite having high 16S rRNA gene sequence similarity to mesophilic bacteria inhabiting various temperate environments, all Lake Fryxell isolates were psychrotolerant, with growth occurring at 0 °C and optimal growth from 18–24 °C for all isolates. Phylogenetic analyses showed the isolates to be members of six taxonomic groups, including the genera Brevundimonas, Arthrobacter, Sphingobium, Leifsonia, and Pseudomonas, as well as the family Microbacteriaceae (one strain could not reliably be assigned to a specific genus based on our analysis). Pseudomonas strain LFY10 stood out as a useful tool for teaching laboratory activities because of its substantial cold adaptation (visible growth is evident in 1–2 days at 4 °C), beta-hemolytic activity, and halotolerance to 8.5% (w/v) NaCl. These cold-adapted bacteria likely play a role in carbon mineralization and other nutrient cycling in Lake Fryxell, and their characterization broadens our understanding of microbial biodiversity in aquatic polar ecosystems.